Market devices and structural dependency: The origins and development of "dark pools" - Donald A. MacKenzie (Finance and Society, 2019)
"Dark pools" are private, electronic share-trading systems in which participants cannot see each other's buy and sell orders. This article shows that the development of these material "market devices" was strongly shaped by the structural dependency of their intended clientele (fund-management firms) on the big investment banks, particularly the indirectly monetary mechanism of dependency known in the US as "soft dollars". The article's underlying argument is that (a) the sociological analysis of financial markets requires bringing together the focus on materiality of, for example, actor-network theory with an emphasis on structural advantage such as that found in field theory; and (b) that both actor-network and field theory approaches could be strengthened by a stronger focus on mundane but important monetary mechanisms such as "soft dollars".
Keywords: 300; Dark pools; market devices; field theory; actor-network theory; social studies of finance